FINANCIAL RATIO ANALYSIS TO ASSESS WORKING CAPITAL EFFICIENCY AT PT. PEGADAIAN FOR 2019-2021 - Nasution, Lily Karlina; Gaudensius Purba (SEAN Institute, 2022)
The results of the study note that the level of working capital efficiency at PT. Pegadaian, is at an inefficient level. It can be seen from the calculation of inventory turnover below standard with an average of 5.97, receivables turnover below standard with an average of 0.27 and working capital turnover of PT. Pegadaian in 2019-2021 has an average of 0.98 under 6 times the working capital turnover.